Guidelines for evaluating web accessibility, level A - Acevedo, Juan J. (2013)
The Web Accessibility Initiative (WAI) defines the guidelines to facilitate access for people with disabilities to ICT. This article presents a proposal to promote the unification and improvement of the works of two authors, combining the procedures and considerations after the evaluation of some web sites Northeast Argentina (NEA).